Economic analysis of solar PV farm efficiency using herbal plots - Othman, Noor Fadzlinda (2016)
Renewable Energy (REs) resources such as wind, solar photovoltaic (PV) and biomass are the future sustainable energy for various industrial applications. In most developing countries especially Malaysia, dependence on fossil fuel like coal, oil and natural gas are at stake. In the near future, these fossil-based energy which are depleting has consistently and produces negative impacts to the environment like global warming and greenhouse gas (GHGs) emissions. Thus, to meet the increasing energy demand, Malaysia needs to shift its energy policies by adapting the REs which assist to protect the environment. Furthermore, the introduction of REs especially solar PV flows in line with green economy requirement.The significant advent of this study is targeted to reveal the economic feasibility of improving solar PV efficiency on Agro-PV project using herbal plots under the PV array with economic viewpoints. As means of strategic approach, Sustainable Energy Development Authority of Malaysia (SEDA Malaysia) has been established under the Sustainable Energy Development Authority Act 2011 with a clear focus on economic development and environment conservation. It visions to deploy sustainable energy measures as part of the solutions towards achieving energy security where it is in line with the scope of this study on agro PV integration. The adaptation of green technologies is important to ensure a sustainable economic growth thus, it should be effectively manage towards greener environment and future development.In conjunction with green growth, renewable technology becomes a new economic driver to effectively manage the food supply and energy demands. The integration of renewable energy in agriculture are addressed via the adaptation of solar PV technologies in high value herbal crops cultivation. The concept of herbal plots under PV structures as the cooling mechanism are also a new technique proposed with significant carbon reduction outcomes. Morphological analysis for four types of potential herbal plants namely Orthosiphon Stamineus, Andrographis Paniculata, Euphorbia Tirucalli and Hibiscus Sabdariffa under this specific condition proves that Orthosiphon Stamineus (Java Tea) as the chosen High Value Herbal crops (HVHc). These scope covers the first objective which is to identify and choose the most suitable herbal crops deployed under solar PV arrays. The second objective is to determine and estimate the relevant cost and benefits elements involved in the project. Then third objective is to assess the economic feasibility of herbal plants as cooling mechanism as reflected in the heat sink concept. This study differentiate the direct and indirect cost and benefit elements of the Agro-PV project. To fulfil the objectives and test the hypotheses, the CBA criteria used are Internal Rate of Return (IRR)), Net Present Value (NPV) and Monte Carlo Simulation (MC-Sim). The study applies the cost-benefit analysis (CBA) framework. Temperature plays a significant role in Solar PV technology and herbal growth where approximately 0.5 % electricity from PV generators are reduced based on 1 °C increase of the module temperature. Some study proves that significant amount of electricity generated from the PV system will be reduce or disperse as heat energy due to the increasing module temperature.Thus this brings the idea of green plants as urban infrastructure. This study suggests cooling effect by herbal plots under Solar PV array justified by means of measured temperature within herbal plant surroundings which are comparatively lower as compared to the mid-air temperature under the solar PV array.The calculation proven that integrating herbal plants under the solar PV array is proven to be economically viable. This study also highlights the existence of cooling mechanism by herbal plant surroundings under the solar PV array which is 0.85 0C much lower as compared to the mid-air temperature. Herbal plants have the ability in absorbing heat discharge from solar PV arrays thus increase the solar PV power conversion efficiency up to 0.425%. The hypothesis is supported by the field of green infrastructure which concludes that strategic positioning of plants could reduce urban heat energy consumption by 20 – 40 %. The Agro-PV Solar Farm gain surplus from the carbon credit scheme that blends smoothly with herbal plots as the cooling mechanism under solar PV arrays.The crucial findings of this work are explained by means of inculcating herbal plots as an effective cooling mechanism in solar PV farms which proves to be technically sound and economically feasible. It is expected to increase the annual Solar PV energy generation up to 2.77 % or RM156k/ year. The Agro-PV concept produces sufficient IRR value of 13.51% with a reduction of one year for ROI. Thus,the information obtained from this study can fill the information gaps via providing field measurement and insights to policy makers and stakeholders for better decision in agro-pv industry.